La calidad de servicio educativo y de atención de los Centros Infantiles del Buen Vivir, perspectivas y expectativas de los padres de familia :Estudio de caso en el CIBV “Domingo Savio” del barrio Álvarez Chiriboga, Parroquia Cayambe, Cantón Cayambe. - Quinchiguango Peñafiel, Elsa María (2014)
This research work was conducted at the CIBV "Dominic Savio" Chiriboga Alvarez neighborhood, parish Cayambe Cayambe Canton; This was done with the participation of teachers, parents and mothers of the institution and the community. It was necessary to analyze the quality of education and infant care centers for Good Living from the perspectives and expectations of parents; taking into account that early childhood is considered the primary stage in human life, where the development of skills and abilities is power.